PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN GENERASI MILLENIAL YANG BERDOMISILI DI RW 11, KELURAHAN CAKUNG TIMUR, KECAMATAN CAKUNG, KOTA JAKARTA TIMUR - NOVIA SULISTYAWATI (2021)
This study is a quantitative study that aims to determine whether there is an influence from the work environment, organizational culture and transformational leadership on the satisfaction of millennial generation employees who live in Rw 011, Cakung Timur Village, Cakung District, East Jakarta City at the place of the company where they currently work. This study used 80 respondents from 160 population of working employees aged 21-39 years. The analysis technique used is the path analysis method and data processing is carried out through SmartPLS 3.3.3 The results of the test are (1) the work environment has a significant effect on job satisfaction of millennial generation employees Rw 011. (2) organizational culture has a significant effect on job satisfaction of millennial generation employees Rw 011. (3) transformational leadership has a significant effect on job satisfaction of millennial employees Rw 011. Keywords : Work Environment, Organizational Culture, Transformational Leadership, Job Sastifaction